Peran Corporate Social Responsibility Disclosure Dalam Memediasi Mekanisme Corporate Governance Dan Earning Management Terhadap Corporate Financial Performance - Luluk Muhimatul Ifada; Siti Istiqomah (Conference In Business, Accounting, And Management (CBAM), 2012)
The corporate social responsibility (CSR) has to be based on triple bottom lines those are social, environmental, and financial. The corporate governance mechanism is represented by managerial ownership, institutional ownership, proportion of independent commissioner board, and existence of audit committee. The objectives of this study is to examine the influence corporate governance mechanism to earnings management, CSR disclosure and corporate financial performance and examines the influence of earnings management to CSR disclosure and corporate financial performance. Beside that, this study also examines the influence of corporate governance mechanism to corporate financial performance mediated by earnings management and CSR disclosure and the influence of earnings management to corporate financial performance mediated by CSR disclosure. Earnings management and CSR as intervening variables in this study. This study takes 84 companies sample by purposive sampling in the manufacturing sector at the Indonesian Stock Exchange, which were published in financial report from 2007-2009. The analysis method used of this research is Partial Least Square (PLS) . The results of this study showed that: (1) corporate governance mechanism have positive correlation but not significant to earnings management and corporate financial performance. (2) corporate governance mechanism have positive significant influence to CSR disclosure. (3) earnings management have positive correlation but not significant to CSR disclosure and corporate financial performance. (4) earnings management and CSR disclosure doesn’t intervening variables in the relation of corporate governance mechanism to corporate financial performance. (5) CSR disclosure doesn’t intervening variable in the relation of earnings management to corporate financial performance.Keyword : Corporate Governance Mechanism, Earnings Management, CSR disclosure, Corporate Financial Performance.